PERKAWINAN TRADISIONAL MASYARAKAT KEI DALAM PERSPEKTIF TEORI KEKERABATAN CLAUDE LÉVI-STRAUSS - Refo, Ignasius SS. (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STPAK St. Yohanes Penginjil Ambon, 2013)
According to Lévi-Strauss, there are two different structural models of marriage exchange. First, the women of Ego's group areoffered to another group explicitly defined by social institutions. This is the elementary structure of kinship. Secondly, the group ofpossible spouses for the women in ego's group is